1995
DOI: 10.1016/0735-1097(95)00141-l
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular blood flow patterns in normal subjects: A quantitative analysis by three-dimensional magnetic resonance velocity mapping

Abstract: The hypothesis of a diastolic vortex formation in the human left ventricle was confirmed, and its close temporal relation to the motion of the anterior mitral leaflet was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
165
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(194 citation statements)
references
References 20 publications
26
165
3
Order By: Relevance
“…The videos were systematically reviewed frame by frame and the resulting flows were examined to testify the reduction of vortex penetration in the LV with the increase of infarct size. In vivo visualization of the actual LV vortex pattern in normal subjects were first recorded by CMR, 54 and the asymmetric sinuous flow paths around the vortex in the human heart were elegantly described shortly after. 51 It was suggested that the asymmetric vortical arrangement is the fluid functional counterpart of the looped heart structure, which enhances the atrio-ventricular mechanical synergy and supports the conservation of momentum from the entry jet to the ejected flow.…”
Section: First Studies On Vortex Formationmentioning
confidence: 99%
“…The videos were systematically reviewed frame by frame and the resulting flows were examined to testify the reduction of vortex penetration in the LV with the increase of infarct size. In vivo visualization of the actual LV vortex pattern in normal subjects were first recorded by CMR, 54 and the asymmetric sinuous flow paths around the vortex in the human heart were elegantly described shortly after. 51 It was suggested that the asymmetric vortical arrangement is the fluid functional counterpart of the looped heart structure, which enhances the atrio-ventricular mechanical synergy and supports the conservation of momentum from the entry jet to the ejected flow.…”
Section: First Studies On Vortex Formationmentioning
confidence: 99%
“…Initially, the term three-dimensional was used to describe a three-directional twodimensional MRI acquisition (29). Later on, 3D cine PC MRI acquisitions have sometimes being referred to as 4D or 7D.…”
Section: Three-dimensional Cine Phase-contrast Mri Acquisitionmentioning
confidence: 99%
“…The numerical scheme of this restoration method [6] can be defined as follows. Firstly, the strength function e(u; ) at voxel can be defined as: (1) where N α denotes the neighbourhood of pixel α and d l denotes the embedded Euclidean distance in S 2 . The TV-energy of the direction field in domain Ω is then: (2) and the constrained optimisation can be written as:…”
Section: Flow Field Restorationmentioning
confidence: 99%
“…In particular, vortical motion, known to exist in the diastolic phase of the cardiac cycle [1], is the most important flow feature and its evolution over different phases of the cardiac cycle can provide important insight into the health status of the heart. Previous research [2] has shown that in order to achieve a comprehensive and integrated description of flow in health and disease, it is necessary to characterise and model both normal and abnormal flows and their effects.…”
Section: Introductionmentioning
confidence: 99%